Trends and future predictions of chronic kidney disease due to diabetes mellitus type 2 attributable to dietary risks: insights based on GBD 2021 data - Xu, Ming; Wei, Hongxia; Lv, Dongqing; Wei, Yanhong; Liu, Ziang; Zhang, Yi; Liu, Yunfeng (Frontiers in Nutrition, 2025)
BackgroundThe 2021 Global Burden of Disease (GBD) study shows a continuous increase in the burden of chronic kidney disease due to diabetes mellitus type 2 (CKD-T2DM) from 1990 to 2021. This study examines the influence of dietary risk factors across various populations and socioeconomic groups.MethodsUtilizing the 2021 GBD data, we analyzed age-standardized CKD-T2DM metrics—including mortality, disability-adjusted life years (DALY), and age-standardized rates (ASR)—stratified by age, gender, and region. The study employs estimated annual percentage changes (EAPC) to monitor temporal trends and project future trends from 2022 to 2035 using bayesian age-period-cohort (BAPC) analysis.ResultsThe results indicate that, in 2021, 20.55% of CKD-T2DM mortality and 23.21% of CKD-T2DM DALY were attributed to poor diets, especially those low in fruits and high in red and high processed meat. Throughout this period, both mortality and DALY rates associated with dietary risks increased significantly, with the most rapid increase in diet high in sugar-sweetened beverages, highlighting the considerable impact of dietary factors on the global CKD-T2DM landscape. Geographic disparities in T2DM trends are evident, with the most significant increases in age-standardized mortality rates (ASMR) and age-standardized DALY rates (ASDR) observed in regions such as high-income North America and Central Latin America. Socio-demographic index (SDI) is negatively correlated with the CKD-T2DM burden attributable to dietary risk factors.ConclusionPublic health interventions that target dietary changes can significantly reduce the global burden of CKD-T2DM.